1994
DOI: 10.1099/00207713-44-4-734
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy of Rhizobium Strains from Legumes of the Temperate Zone

Abstract: Phenotypic properties (growth characteristics, utilization of carbon and nitrogen sources, and intrinsic antibiotic resistance) of 53 Rhizobium strains isolated from root nodules of the temperate-zone legumes Astragalus spp. (29 strains), Oxytropis campanuhta (7 strains), Hedysarum alpinum (7 strains), Ononis awensis (3 strains), Glycyrrhiza spp. (4 strains), and Coronilh varia (3 strains) were compared with those of other Rhizobium, Bradyrhizobium, and Agrobacterium strains. The final matrix, containing 83 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…The RFLP analysis showed very few bands in common between the diverse isolates and the inoculant strain, both at the whole genome level as revealed by Spe I digests and in localized regions of the chromosome as revealed by hybridizations of EcoRI digests to cosmids containing genes involved in exopolysaccharide synthesis and to randomly cloned fragments. R. loti is a heterogeneous species with some isolates that nodulate L. corniculatus sharing as little as 47% DNA-DNA homology (22) and little phenotypic similarity (44). This heterogeneity is reflected in 16S rRNA gene sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RFLP analysis showed very few bands in common between the diverse isolates and the inoculant strain, both at the whole genome level as revealed by Spe I digests and in localized regions of the chromosome as revealed by hybridizations of EcoRI digests to cosmids containing genes involved in exopolysaccharide synthesis and to randomly cloned fragments. R. loti is a heterogeneous species with some isolates that nodulate L. corniculatus sharing as little as 47% DNA-DNA homology (22) and little phenotypic similarity (44). This heterogeneity is reflected in 16S rRNA gene sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences from most nodule strains had a 1-bp substitution from the type strain but one had three substitutions and was identical to sequence from the type strain of R huakuii. There is normally little or no variation in 16S sequence within a bacterial species (45,46) and so the degree of variability in 16S sequence observed, together with the range in overall relatedness (22,44) (25,26) and can be cured without adversely affecting nodule formation (26,27), inferring a chromosomal location for the symbiotic genes. We did not detect plasmids in the inoculant strain or most nodule isolates and the transferred DNA seemed to be chromosomally integrated, as shown by the strain-specific pattern obtained from hybridization of nod gene probes to genomic DNA digests generated by the rare-cutting enzyme Swa I (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of REP-PCR profiles for different habitats revealed levels of similarity among isolates that ranged from 80% to less than 60%. Similarly, other authors found considerable genetic diversity among rhizobia nodulating L. corniculatus by using other methodological approaches, like DNA-DNA hybridization (11,29,30) or numerical taxonomy (48).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity among rhizobia from Astragalus adsurgens in different geographical regions of China has been investigated, and bacterial lineages related to Mesorhizobium, Rhizobium and Sinorhizobium were reported (Gao et al, 2001). Different rhizobial groups were also defined among isolates from other Astragalus species in China (Wang & Chen, 1996) and in other countries (Laguerre et al, 1997;Murooka et al, 1993;Novikova et al, 1994;Wdowiak & Malek, 2000).…”
Section: Introductionmentioning
confidence: 99%